Comprehensive Genomic and Immunohistochemical Profiling to Predict Prognosis and Recurrence in Fertility-Sparing Therapy Based on Progesterone for Endometrial Carcinoma - Lin Yang PhD; Yufei Nie PhD; Hongyan Guo PhD (Technology in Cancer Research & Treatment)
Background Endometrial carcinoma (EC) represents a unique clinical challenge. Fertility-sparing treatments rely on achieving complete response (CR) through progesterone-based therapy. We sought to investigate the prognostic value of molecular subtyping and immunohistochemical (IHC) markers in predicting three-month treatment outcomes and recurrence in EC patients undergoing fertility-sparing therapy. Methods A retrospective cohort of 68 patients diagnosed with early-stage EC received hysteroscopic surgery and conservative treatment whose paraffin-embedded tissue blocks preserved in our hospital between Jan. 2010 and Oct. 2022 was evaluated. Molecular subtyping based on TCGA classification identified low copy-number (CNL), microsatellite instability-high (MSI-H), and copy-number high (CNH) subtypes. IHC markers, including PTEN, PIK3CA, β-catenin, ARID1A, estrogen receptor (ER), and progesterone receptor (PR) were analyzed for their association with CR and recurrence. Transcriptome sequencing gene chips were used to study patients who achieved or did not achieve CR after three months, those who experienced recurrence within one year, and those who did not recur within two years. Differential genes were then mapped to KEGG pathways to explore the underlying mechanisms of progesterone therapy efficacy. Results Among the 68 patients classified through TCGA molecular typing, 65 cases (95.6%) were CNL subtype, two (2.9%) were MSI-H subtype, and one (1.5%) was CNH subtype. Following a three-month treatment, the CR rate for the CNL subtype was 75.4% (49/65), the MSI-H subtype was 50.0% (1/2), and the CNH subtype was 0% (0/1). In CNL subtype endometrial carcinoma, individuals with high PTEN and PR expression were more likely to achieve CR after three months ( P  < .05). Conversely, those with elevated CA199 levels and increased PIK3CA expression were more prone to recurrence after CR. Conclusion MSI-H and p53-mutant subtypes of endometrial carcinoma are not suitable for fertility preservation therapy. PTEN/PI3K-AKT-mTOR pathway activation contributes to reduced progesterone sensitivity, underscoring the need for targeted therapeutic strategies to improve patient outcomes.